Sprawozdanie z I Seminarium Naukowców i Praktyków „Instrumenty finansowo-prawne w ochronie środowiska” formuła hybrydowa, Szczecin 7 grudnia 2023 roku - Paulina Jachimowicz-Jankowska (Studia Administracyjne)
On June 13, 2024, the 1st Seminar of Scientists and Practitioners entitled "Financial and legal instruments in environmental protection" was held, organized by the Environmental Protection Law Research Team, the Faculty of Law and Administration of the University of Szczecin and the scientific journal Administrative Studies. This event was conducted remotely via MS Teams.